THE EFFECT OF MASSAGE AND MUSIC THERAPY FOR PREMATURE INFANTS: A LITERATURE REVIEW - Lia Dian Ayuningrum; Mardelia Astriani (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Premature infants are prone to loose skin stimulation through skin contact with the amniotic fluid and the uterine wall of the mother during the intrauterine phase. This situation becomes one of the decisive factors in the growth and development of infants’ nerves. In addition to the initial sensory deficiency, prematurity raises other related factors such as the absence of bonding between the mother and the newborns due to the need to remain in the neonatal intensive care unit (NICU). Prematurity also has adverse effects on the psychological and biological development of the children and the parents’ welfare. Aims: The aim of this study was to analyze the literature relating to holistic care in massage and music therapy for premature infants and summarize the benefits of both therapies. Methods: The method used in finding articles was a literature review, using the keywords. Search was conducted electronically using several databases, including Pubmed, Science Direct, and Google Scholar Conclusion: Massage and music therapy have benefits for premature infants growth. Keywords: Premature infants, preterm, massage therapy, music therapy